2021
DOI: 10.3233/bmr-200010
|View full text |Cite
|
Sign up to set email alerts
|

Intra-rater and inter-rater reliability of neutral and target lumbar positioning tests in subjects with and without non-specific lower back pain

Abstract: BACKGROUND: Proprioception, one’s sense of movement and position, is a common term used in back rehabilitation. Kinesthetic rehabilitation may be useful in managing lower back pain; however, reliable measures are required to quantify lumbar proprioception sense. OBJECTIVE: To investigate intrarater and interrater reliability of neutral lumbar positioning (NLP) and target lumbar positioning (TLP) tests and compare the position sense errors in subjects with non-specific low back pain and healthy controls. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…The accessories include three velcro straps, an assembly wire connecting the inclinometers, and two metal plates to align the inclinometer unit. The digital inclinometer had a significant level of validity compared with an isokinetic dynamometer (ICC = 1.0, SEM = 1.39, p < 0.001) and also showed excellent intra- and inter-tester reliability for measuring JPS (ICC = 0.994, SEM = 1.67, p < 0.001) [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The accessories include three velcro straps, an assembly wire connecting the inclinometers, and two metal plates to align the inclinometer unit. The digital inclinometer had a significant level of validity compared with an isokinetic dynamometer (ICC = 1.0, SEM = 1.39, p < 0.001) and also showed excellent intra- and inter-tester reliability for measuring JPS (ICC = 0.994, SEM = 1.67, p < 0.001) [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Decreased proprioceptive acuity might lead the hypermobile joints to instability and increased risk of injury ( Smith et al, 2013 ). In addition, previous research demonstrates that impaired proprioception is crucial in developing and maintaining pain, tissue injury, and degenerative joint diseases ( Alahmari et al, 2020a ; Alahmari et al, 2017b ; Alahmari et al, 2017c ; Asiri et al, 2021 ; Kristjansson & Treleaven, 2009 ; Reddy et al, 2021a ; Reddy et al, 2020 ). Therefore, assessing cervical proprioception is vital in evaluating and managing subjects with GJH.…”
Section: Introductionmentioning
confidence: 99%
“…Third, sitting in an unequal position for a long period of time causes back pain [19]. The lumbar proprioceptive sense is diminished in people who experience non-specific low back pain [20], and pain inhibition of local muscles like the lumbar multifidus can cause changes in the muscle recruitment patterns, affecting the neuromotor system, altering dynamic spine stabilization, and resulting in repositioning deficiencies, as seen by the low back pain that arose from sitting cross-legged for a prolonged time can produce alterations in spinal posture, indicating the possibility of pelvic pain [15,21], and Röijezon et al [6] reported that altered proprioception has been linked to pain.…”
Section: Discussionmentioning
confidence: 99%